Prevalence and impact of asthma in schoolchildren in the city of Caxias do Sul‐RS - Daniel Zacaron; Cristian Roncada; Rossano Sartori Dal Molin; Marcus Herbert Jones; Paulo Condessa Pitrez (Brazilian Society of Pediatrics, 2020)
Objective: To analyze the prevalence and impact of asthma in schoolchildren from the city of Caxias do Sul, RS, Brazil. Methods: Cross‐sectional observational and case‐control study with children and adolescents between 7 and 15 years old, from public schools in Caxias do Sul/RS. The study is composed of two phases: Phase I analyzed the prevalence of asthma in the delimited population investigating 1915 schoolchildren; Phase II quality of life questionnaires, asthma control and classification (for the asthmatic group), physical activity, school performance, pulmonary function tests and anthropometric measures were applied to 266 asthmatics and 288 controls. Results: The estimated prevalence of asthma was 16.1%. In the comparison between asthmatics and nonasthmatics premature birth (p < 0.001) and diagnosis of another chronic disease at birth (p < 0.001) were found. Regarding pulmonary function, significant differences were found in the values between groups in FEV1, FEV1/FVC and forced expiratory flow in the 25 and 75% moments (FEF25‐75%), being that asthmatics presented lower values. Among asthmatics, 133 (50.8%) did not have the disease controlled. In the anthropometric variables, significant differences were observed, with higher values in controls, in the waist‐to‐height ratio (p = 0.009) and in the perception of health (p < 0.001). Quality of life is lower in asthmatics in the physical well‐being domain (p = 0.001) and in the total score (p = 0.016). The total school performance score did not present a statistically significant difference between the study groups. Conclusion: The prevalence of asthma is similar to that of other industrialized urban centers and may negatively affect some areas of the development of schoolchildren. Resumo: Objetivo: Analisar a prevalência e o impacto da asma em escolares do município de Caxias do Sul‐RS. Métodos: Estudo analítico observacional transversal e caso‐controle, com crianças e adolescentes entre sete e 15 anos, de escolas da rede pública de Caxias do Sul‐RS. O estudo é composto por duas fases: Fase I analisou a prevalência da asma na população delimitada e investigou 1.915 escolares; Fase II foram aplicados a 266 asmáticos e 288 controles, questionários de qualidade de vida, classificação e controle da asma (para o grupo asmático), atividade física, desempenho escolar, espirometria e antropometria. Resultados: A prevalência de asma estimada foi de 16,1%. Na comparação entre asmáticos e não asmáticos foram encontradas diferenças na prematuridade (p< 0,001) e ter diagnóstico de outra doença crônica ao nascer (p< 0,001). Na espirometria foram encontradas diferenças significativas entre os grupos nos valores de VEF1, VEF1/CVF e fluxo expiratório forçado nos momentos 25 e 75% (FEF25‐75%); os asmáticos apresentaram valores inferiores. Entre os asmáticos, 133 (50,8%) não tem a doença controlada. Nas variáveis antropométricas foram observadas diferenças significativas, com valores superiores entre os controles, na classificação razão cintura/estatura (p = 0,009) e na percepção da própria saúde (p< 0,001). A qualidade de vida é menor nos asmáticos no domínio bem estar físico (p = 0,001) e no escore total (p = 0,016). O escore total do desempenho escolar não apresentou diferença estatisticamente significativa entre os grupos de estudo. Conclusão: A prevalência de asma se assemelha à de outros centros urbanos industrializados e pode impactar negativamente alguns domínios do desenvolvimento dos escolares.